Risk Factors of Diarrhea in Toddlers at Andi Makkasau Hospital Parepare City - Ashar, Astahsan; Majid, Makhrajani; Dwi Putri Rusman, Ayu (Riviera Publishing, 2023)
Diarrheal disease is a major problem in developing countries, including Indonesia. Aside from being a cause of death, diarrhea is also a major cause of malnutrition which can lead to death. Besides being caused by malnutrition, in terms of public health science, there are other factors related to the incidence of diarrhea. The dominant factors causing diarrhea in Indonesia are clean water, sanitation, and feces disposal facilities. This study aimed to determine the risk factors for diarrhea in toddlers at Andi Makkasau Hospital, Parepare City. Analytical survey research methods and case-control study designs. The sampling technique used purposive sampling. This study's sample was all children under five treated at Andi Makkasau Hospital, Parepare City, namely as many as 50 toddlers. The sample was divided into two groups, where 25 toddlers were in the case group (diarrhea), and 25 were in the control group (no diarrhea). Data analysis used the Odds Ratio (OR) test. The results obtained from the risk factors for diarrhea in toddlers are the availability of clean water (OR=1.263), hand washing habits (OR=1.658), food sanitation (OR=3.273), availability of healthy latrines (OR=17.250) and management garbage (OR=5,762). This study concludes that clean water, hand washing habits, food sanitation, availability of healthy latrines, and waste management are risk factors for diarrhea in toddlers at Andi Makkasau Hospital, Parepare City. Parents are expected to improve clean living behavior to prevent diarrheal disease in toddlers.